An Analysis of 400 Sternal Wound Reconstructions at a Single Institution: Bacterial Pathogens Vary With Time. (May 2022) - Kuonqui, Kevin; Levy, Adam S.; Tiao, Jonathan R.; Altchek, Chloe; Ascherman, Jeffrey A.
Abstract : Background: Sternal wound (SW) infection and dehiscence after median sternotomy from cardiac surgery remain challenging complications with high morbidity. Knowledge of common pathogen types and variance with time from cardiac surgery can simplify the choice of antibiotics while awaiting definitive culture results. Methods: Records of 505 patients undergoing SW reconstruction by the senior author from 1996 to 2018 at a high-volume cardiac surgery center were reviewed. The most common indications for reconstruction were SW infection and dehiscence. At surgery, all patients underwent removal of sternal hardware, thorough debridement, and closure with bilateral pectoralis major myocutaneous advancement flaps. Deep tissue and bone cultures were sent in nearly all cases. Patients were split into group 1 or group 2 based on timing of flap reconstruction after initial cardiac surgery: 0 to 30 days and longer than 30 days, respectively. Results: Complete data were available for 400 SW procedures performed during this period. Group 1 included 203 patients, and group 2 had 197 patients, with a mean time to SW surgery of 16.3 and 138.1 days, respectively. Intraoperative cultures were positive in 147 of 203 (72.4%), and 122 of 197 (61.9%) patients, respectively. Forty-four patients grew polymicrobial cultures. There was a significant difference in culture positivity rates in the 2 groups ( P = 0.0004). The most common bacteria cultured in group 1 was Staphylococcus epidermidis (54 of 203 vs 21 of 197; P < 0.0001), whereas methicillin-sensitive Staphylococcus aureus was most common in group 2 (15 of 203 vs 22 of 197; P = 0.23). Methicillin-resistant S. aureus was relatively common in both groups (17 of 203 vs 21 of 197; P = 0.50). Although not statistically significant, Pseudomonas, Klebsiella, and Candida were all found in a higher percentage of patients in group 2 (p = 0.11, 0.20, 0.20). Conclusions: Microbial species cultured in SW flap reconstruction vary over time. Staphylococcus epidermidis is the most common infectious agent in patients having reconstruction within 30 days of cardiac surgery, whereas methicillin-sensitive S. aureus is most common after 30 days. The trend toward a higher incidence of Gram-negative and fungal organisms after 30 days may indicate a need for broader initial anti-infective coverage in this patient group. Awareness of these pathogen patterns can better inform antibiotic selection while awaiting culture data.